(untitled) (International Journal of Environmental Sciences, 2025)
In this paper, we introduce a new class of spaces referred to as Pythagorean fuzzy nano normal spaces, including their variants: , , , and -normal spaces. We also define their corresponding strongly Pythagorean fuzzy nano normal spaces. These spaces are formulated using the respective types of Pythagorean fuzzy nano open sets within the framework of Pythagorean fuzzy nano topological spaces. Furthermore, we explore the relationships among these newly defined spaces and their connections with existing spaces. Additionally, we study their basic properties and provide characterizations of the introduced normal spaces.